Chronic Hypoxia Emerging as One of the Driving Forces behind Gene Expression and Prognosis of Hepatocellular Carcinoma. (22nd May 2011) - van Pelt, Jos F.; van Malenstein, Hannah; Nevens, Frederik; Verslype, Chris
Abstract : Hepatocellular carcinoma (HCC) is one of the most frequent malignant tumors and an important cause of death. It has become evident that the tumor microenvironment, including hypoxia, plays a major role in the development of HCC. This paper focuses on the role of chronic hypoxia in HCC. Recently, we have shown the importance of chronic hypoxia on gene expression and behavior of liver cells. Using a cell culture model, we identified a distinct gene expression pattern and demonstrated clinical relevance for a 7-gene subset that can predict survival and early recurrence in patients. Recently, it was also shown that chronic hypoxia is associated with the upregulation of β -catenin and Hif1 α and that suppression of β -catenin reduced the metastatic potential of the tumor. Both studies demonstrate the importance of chronic hypoxia for the prognosis of HCC. Identifying the molecular pathways can help us to understand the mechanisms responsible for tumor aggressiveness.